Intraosseous schwannoma localized in the anterior mandible with multilocular radiolucency: A case report. Issue 2 (5th March 2016) - Kawasaki, Yasuhiro; Kobashi, Hironobu; Ishii, Syouichirou; Yakushijib, Noboru
Abstract: Intraosseous schwannoma in the oral and maxillofacial regions is rare. It arises most commonly in the posterior region of the mandible due to the presence of the inferior alveolar nerve. There have been only seven reported cases of intraosseous schwannoma localized in the anterior region of the mandible, all of which involved unilocular radiolucency. In this study, we report the rare case of an intraosseous schwannoma localized in the anterior mandible with multilocular radiolucency. The radiographic and clinical features of this case may be helpful for providing a correct diagnosis and treatment in the future.